Development and validation of a ready to use cryo-EROD assay for the standardized screening of dioxins and dioxin-like compounds in foodstuffs. (December 2018) - Levy, Walkiria; Schramm, Karl-Werner; Mertes, Florian; Henkelmann, Bernhard; Maywald, Martina; Uciechowski, Peter; Loa, Alexander; Haedrich, Johannes; Thiem, Ines; Hollert, Henner; Goerlich, Roland; Bernsmann, Thorsten; et al.
Abstract: Recent European regulations have indicated the need for new bioanalytical screening methods capable of monitoring dioxin and dioxin-like compounds in foodstuffs and environmental samples, cost-effectively and with a quicker turnaround. Cryo-cells of the hepatic H4IIE line preserved in 96-well plates were exposed to sample extracts prepared from various foodstuffs and analysed for their content of dioxins and dioxin-like compounds by means of the 7-Ethoxyresorufin- O -Deethylase (EROD)-assay in two laboratories. Assay data were compared between both laboratories and results from instrumental analysis used as a confirmatory method. Additionally, cut-off values for the different studied matrices were derived. The current European regulation regarding methods of analysis for the control of foodstuffs was applied with the aim of determining the feasibility of the cryo-methodology. Results obtained in both laboratories were in congruence with the required validation parameters of the Commission Regulation (EU) No 2017/644. Cut-off values should be established matrix-dependent to reduce the rate of false compliant results and to keep the rate of false non-compliant results under control. In summary, the ready-to-use cryo-assay method for the bioanalytical screening of foodstuffs in control laboratories without cell-culture facilities has successfully proven to be accurate, far quicker and more cost effective than current methods. Highlights: A novel method for bio-screening of dioxin and dioxin-like compounds was carried out in various foodstuffs. The cryo-assay validation was successfully performed based on the current European regulations. Toxicity and antagonistic effects that generate potential false-compliant samples were analysed. Cut-off concentrations should be established based on sample matrix and laboratory performance. Food control laboratories with basic cell culture facilities can easily use this new cryo-EROD assay.